The Strength of the Lower Trapezius in Violinists With Unilateral Neck Pain - Kim, Si-Hyun; Park, Kyue-Nam (Han'guk Chŏnmun Mulli Ch'iryo Hakhoe chi = Journal of the Korean Academy of University Trained Physical Therapists, 2014)
Violinists tend to position the neck asymmetrically to hold the violin between the chin and the left shoulder. Asymmetrical neck posture may induce unilateral neck pain. Previous studies have suggested that individuals with unilateral neck pain exhibit reduced muscle strength of the lower trapezius, but no study has investigated violinists with unilateral neck pain. To this end, we recruited 18 violinists with unilateral neck pain for the present study in which the side on which neck pain was experienced, pain duration, and intensity were recorded. Lower trapezius strength was measured bilaterally in each subject using a handheld dynamometer. Significant differences in lower trapezius strength were evident between the ipsilateral and contralateral sides of neck pain (p<.05). No significant association between neck pain intensity or duration, and the extent of a deficit in lower trapezius strength, was evident (both p>.05). The association between the sides of weakened lower trapezius strength and neck pain was significant (p<.05). In conclusion, violinists with unilateral neck pain exhibited significantly less lower trapezius strength on the ipsilateral compared to the contralateral side of the pain. Unilateral neck pain more frequently involved the left side of the neck, which is used to stabilize the violin during playing. Thus, our study suggests that a possible relationship exists between muscle weakness in the lower trapezius and neck pain. KCI Citation Count: 0